Basin‐scale environmental water delivery in the Murray–Darling, Australia: A hydrological perspective. (2nd April 2018) - Stewardson, Michael J.; Guarino, Fiorenzo
Abstract: A major outstanding challenge for environmental flow management is to move from a single site, reach or river focus to planning and delivering environmental flows across entire river basins. There is a need for case studies of basin‐scale environmental water delivery as a first step in understanding and eventually generalising basin‐scale responses. The Commonwealth Environmental Water Holder manages a portfolio of water entitlements for protecting and restoring aquatic ecosystems of the Murray–Darling Basin (MDB). This article describes the strategies used by the water holder and the hydrological outcomes of their basin‐scale environmental water delivery program. There are five delivery strategies used to enhance benefits achieved with available environmental water. Although the volume of commonwealth environmental water is small relative to mean catchment inflows, improvements in baseflows and freshes are seen across the MDB. Water was also successfully delivered into floodplain wetlands. The case study provides a successful example of implementing a basin‐scale program for environmental water delivery. However, there remains a great need to improve the knowledge, governance and planning tools for managing environmental water for a broad range of ecological demands that operate at the basin‐scale.